2017
DOI: 10.1007/s40139-017-0125-y
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Immunology Viewed from Alternative Animal Models—the Xenopus Story

Abstract: a) Purpose of review Nonmammalian comparative animal models are important not only to gain fundamental evolutionary understanding of the complex interactions of tumors with the immune system, but also to better predict the applicability of novel immunotherapeutic approaches to humans. After reviewing recent advances in developing alternative models, we focus on the amphibian Xenopus laevis and its usefulness in deciphering the perplexing roles of MHC class I-like molecules and innate (i)T cells in tumor immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Recent investigations have indicated that pathogenic factors (such as by chytrid fungus and Ranavirus) are causing amphibian population decline and threaten global biodiversity [25][26][27][28][29][30][31]. This further emphasizes the need to study the amphibian immunome and its interaction with epidemic pathogens [1][2][3][32][33][34][35][36][37][38][39][40]. Amphibians have several unusual characteristics that are stimulating for immunobiological studies [32,33,35,39].…”
Section: Ifn-mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent investigations have indicated that pathogenic factors (such as by chytrid fungus and Ranavirus) are causing amphibian population decline and threaten global biodiversity [25][26][27][28][29][30][31]. This further emphasizes the need to study the amphibian immunome and its interaction with epidemic pathogens [1][2][3][32][33][34][35][36][37][38][39][40]. Amphibians have several unusual characteristics that are stimulating for immunobiological studies [32,33,35,39].…”
Section: Ifn-mentioning
confidence: 99%
“…This further emphasizes the need to study the amphibian immunome and its interaction with epidemic pathogens [1][2][3][32][33][34][35][36][37][38][39][40]. Amphibians have several unusual characteristics that are stimulating for immunobiological studies [32,33,35,39]. For example, amphibians have moist and permeable skin, which also serves as an organ for respiration [33,34].…”
Section: Ifn-mentioning
confidence: 99%
See 2 more Smart Citations
“…We developed a Xenopus model in which we could study braindependent events in embryogenesis: the brain is removed during early embryonic stages, but the animal can be kept alive and development continues. The ability of this vertebrate, a popular model for numerous biomedical contexts, [27][28][29][30][31][32][33][34] to survive and develop without a brain provides a unique opportunity to understand the role of the brain in diverse systems-level outcomes. Our prior research into brain-dependent developmental signaling revealed that the nascent brain, even before being fully formed, plays an instructive role in patterning somitic muscle and peripheral neural networks.…”
Section: Introductionmentioning
confidence: 99%